Editorial. Issue 1 (1st March 2015) - Wilkinson, Nicholas
Abstract : We continue our policy of theme issues and open issues twice a year. This particular open issue contains manuscripts on Community Participation, Real Estate Development, Housing Poverty, Dual Usage Sociability, Formal and Spatial Contemporary Transformation, Experimentation with Hanoks in Korean Housing, Infill Renovation and Post Ecological Architecture. These are based in a range of different countries from Hong Kong, Shanghai, Jordan, Turkey, Korea, to Japan. The inquiries are deep and thorough, maintaining a firm grip on subject matter and focus.